MODEL PROBLEM BASED LEARNING (PBL) MENGGUNAKAN E-LKPD UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI LISTRIK STATIS DI SMP NEGERI 1 NANGA TAMAN - Christa Leminara Agustine; Erwina Oktavianty2, Firdaus (Jurnal Riset Multidisiplin Edukasi, 2026)
Purpose – The purpose of this study was to determine the improvement in students’ learning outcomes at SMP Negeri 1 Nanga Taman through the implementation of the Problem Based Learning (PBL) model using E-LKPD on the topic of static electricity. Design/methods/approach – The improvement in students’ learning outcomes was measured using pre-test and post-test instruments consisting of multiple-choice and essay questions. The sample in this study consisted of 25 students from class IX D. The research method used was a pre-experimental design with a one-group pretest–posttest design. Based on the research that has been conducted, an increase in students’ learning outcomes was obtained before and after the implementation of the Problem Based Learning model using E-LKPD. Findings – The results showed that students’ learning outcomes before and after receiving treatment using the Problem Based Learning model increased significantly. The average score of students’ learning outcomes before the treatment was 39.2, while after the treatment it increased to 90.2. The implementation of the Problem Based Learning (PBL) model proved to be effective in improving students’ learning outcomes with an N-Gain value of 0.84, which is categorized as very high. Research implications/limitations – The use of the Problem Based Learning model is effective in improving students’ learning outcomes. However, previous studies have rarely utilized E-LKPD as a learning medium. Therefore, this study applied the Problem Based Learning model assisted by E-LKPD to improve students’ learning outcomes in the topic of static electricity at SMP Negeri 1 Nanga Taman.